Use Of Special Exercises In Developing The Strength Of Wrestlers - pcadmin, I.B.Matmuratova (Genius Journals, 2025)
This article discusses the effective organization of the training process through the effective use of special tools to improve the physical, technical-tactical and psychological preparation of wrestlers, and to develop the quality of strength.
Keywords: technique; wrestlers; wrestling